Feasibility of the Sabellarid Reef Habitat Restoration - Franzitta, Giulio; Colletti, Alberto; Savinelli, Beatrice; Lo Martire, Marco; Corinaldesi, Cinzia; Musco, Luigi (Frontiers in Marine Science, 2022)
Polychaetes of the genus Sabellaria (Annelida, Sabellariidae) are gregarious bioconstructors that build reefs by assembling rigid tubes with sand grains in shallow waters. Sabellarid bioconstructions provide important ecosystem services such as sediments stabilization, water filtration and the mitigation of coastal erosion as well as nursery areas, shelter and feeding grounds for several marine species. Moreover, sabellarid reefs are exposed to both natural and anthropogenic disturbance and are therefore listed by international directives among the marine habitats deserving protection. We conducted a pilot study to assess the feasibility of habitat restoration with the sabellarid reef through a novel transplantation method. Fragments of S. spinulosa reef were collected at 1 m depth, fixed using epoxy putty into terracotta vases and then attached on the landward side of the two breakwaters in a coastal marine area enclosed in a Site of National Interest (SNI) of the central-western Adriatic (Mediterranean Sea). Overall, 14 of the 24 transplanted fragments (54.2 %) survived during the study period (17 months). The total area of the transplanted reef fragments reduced during the early phase, appearing stable toward the end of the experiment. The transplantation method resulted effective given the survival rate observed, however, we did not observe the expected increase in the reef surface. Small-scale variation in environmental conditions such as organic load, sediment granulometry, hydrodynamics might have affected the growth capacity of the transplanted reef fragments. Further studies considering the microscale environmental requirements of this species are needed to better understand the feasibility of sabellarid reef restoration and its large-scale implementation.